Om kritik - Fällbom, Celina (2006)
How does the criticism of landscape architecture in Swedish professional journals look today? Does it exist at all? What is criticism and what is its purpose? These questions have been the starting point for this degree project. I have found a lot of different answers among journals, books and websites, as well as in interviews with five persons that all have a relation to the landscape architecture criticism in different ways. These answers may look a bit disjointed at first, but are at a closer examination pointing in the same direction – that the criticism of landscape architecture projects hardly exists today. The criticism that exists is shallow, unnecessarily subjective and lacks parallels andcomplexity. My research has shown that criticism has three mayor functions – to describe, interpret and to evaluate – and that the purpose of the criticism is to bring the creative process and its consequences in to the light for the creative person to see, and thereby develop the discipline itself. There is a tendency that it is the interpreting part of the criticism that is missing in most cases. This is very unfortunate since this probably is the part that develops the landscape architecture the most, by emphasizing aspects that are not obvious at once. The landscape architecture criticism that after all does exist today tends to appear more frequently in newspapers than in professional journals. It also usually deals with big scale town planning rather than specific projects.